2020
DOI: 10.3390/su12156135
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Sensation in Courtyards: Potentialities as a Passive Strategy in Tropical Climates

Abstract: Climate change will bring changes to our living conditions, particularly in urban areas. Climate-responsive design strategies through courtyards can help to moderate temperatures and reduce the thermal stress of its occupants. Thermal response inside courtyard is affected not only by its morphological composition but also by subjective factors. Thus, standardized thermal scales may not reflect the stress of the occupants. This study investigated the impact on thermal attenuation provided by a courtyard located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In any case, if the tolerance parameter is increased to tol = 3 • C for that case, we obtain the higher percentage 74.40%. On the other hand, the values for the statistical parameters that indicate that the simulation is accurate are R → 1 , RMSE → 0 , MAPE → 0 [36,[42][43][44][50][51][52]. The values of these parameters for the courtyard measured temperature in the present courtyards for each simulation confirm that the used strategy is rather accurate.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In any case, if the tolerance parameter is increased to tol = 3 • C for that case, we obtain the higher percentage 74.40%. On the other hand, the values for the statistical parameters that indicate that the simulation is accurate are R → 1 , RMSE → 0 , MAPE → 0 [36,[42][43][44][50][51][52]. The values of these parameters for the courtyard measured temperature in the present courtyards for each simulation confirm that the used strategy is rather accurate.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies have shown the influence of outdoor temperature and geometry on the thermal tempering potential of the courtyard [49] and their thermal sensation [50], so for this research, a selection of case studies with different outdoor temperatures and different AR (Equation (1), defined in (1)) are analyzed. Therefore, two values, ARI and ARII, are defined.…”
Section: Location Climate and Cases Studymentioning
confidence: 99%
“…The geometry of the courtyard is a fundamental aspect to take into account in the study in addition to the climatic characteristics defined by the location. Previous studies confirm the importance of the relationship between the height (H) and width (W) of the courtyard, known as the aspect ratio (AR) [24] (Equation (1)). Aspect ratios of both courtyards are described in Table 1.…”
Section: Case Studies Location and Climate Descriptionmentioning
confidence: 85%
“…Diz-Mellado et al [8] used thermal comfort modeling to highlight the thermal performance and usability of courtyards in hot climates and demonstrated how courtyards are used to promote thermal comfort in large spaces by casting shadows. Meanwhile, Callejas et al [9] found that courtyard design had a passive cooling impact on internal and external courtyards. Tafti et al [10] concluded that sunken courtyards could offer comfortable temperatures, thereby increasing attention and creativity throughout the summer.…”
Section: Introductionmentioning
confidence: 99%